ANALISIS POTENSI KAWASAN PESISIR PANTAI KOTA PADANG SEBAGAI WISATA OLAHRAGA MARATON BERSKALA INTERNASIONAL - Heru Pramudia (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
Lately, the coastal city of Padang has been improving and being promoted. One of the efforts that can advance tourism is through the introduction and development of national and international sports tourism such as marathons. Marathon is one of the popular sports, such as the New York City Marathon, Parias Marathon, Asia Tokyo Marathon, Tour De France, Bali sailboat competition. This research includes mapping the potential of international scale marathon tourism, how to analyze the potential of sports tourism and the obstacles in the development of sports tourism in the city of Padang. In this study, researchers observed coastal locations that have the potential to develop marathon tourism tourism by looking at the level of tourist development, information on potential locations obtained from informants / informants, these locations have been tested and used for marathon tourism. The internal potential of this marathon sports tour is "high potential" to be held with the quality of marathon tourist attractions and tracking conditions are very good. External potentials include accessibility; object support facilities; complementary facilities, and object development support, this is "high potential" for holding International-scale Marathon Tourism activities. Marathon tourism can be held with a variety of competition criteria by participating in the role of the surrounding community; provide packages offering attractive activities of all ages, clear supporting facilities information; widely introduce to the public a series of marathon tourism activities. The 10K track with diverse contours offers sports and tourism experiences; several narrow road spots so as not to be filled by vehicles or the activities of the local community; the track route is a public area, the number of alternative routes can be used for road transfers; the field committee is able to coordinate public vehicle traffic during the event. Alternative roads and parking areas to be managed by involving local communities so that activities run smoothly. The government helps manage community business activities; avoid illegal payments so as to provide comfort for tourists; parking area prepared to anticipate the emergence of wild parking; education and sanctions for people who do not maintain cleanliness and sanction if there is extortion. Promotion of tourism and sports activities to be further intensified through all media publications; provide opportunities for local EOs and professional EOs to collaborate in the learning process; promotion and clear and mutually beneficial cooperation relationships.